Free indirect style in modernism : representations of consciousness - Rundquist, Eric (Linguistic approaches to literature, 2017)
Free Indirect Style (FIS) is a linguistic technique that defies the logic of human subjectivity by enabling readers to directly observe the subjective experiences of third-person characters. This book consolidates the existing literary-linguistic scholarship on FIS into a theory that is based around one of its most important effects: consciousness representation. Modernist narratives exhibit intensified formal experimentation and a heightened concern with characters? conscious experience, and this provides an ideal context for exploring FIS and its implications for character consciousness. This book focuses on three novels that are central to the Modernist canon: Virginia Woolf?s 'To the Lighthouse', D.H. Lawrence?s 'The Rainbow' and James Joyce?s 'Ulysses'. It applies the revised theory of FIS in close semantic analyses of the language in these narratives and combines stylistics with literary criticism, linking interpretations with linguistic features in distinct manifestations of the style.0.